Perceived social support and its relationship to depression among patients with infectious diseases - ghonoun, gkhemissa (Journal of Social Sciences and Humanities, 2016)
This study aims to investigate the correlational relationship between perceived social support and depression. The study was conducted on a sample of sixty patients diagnosed with hepatitis C at the university hospital of Batna Province. The Perceived Social Support Scale developed by Gregory D. Zimet and the Beck Depression Inventory were administered to the participants. The results of the study revealed a negative correlation between the two variables, as well as the absence of statistically significant differences attributable to gender in both perceived social support and depression.